Professional development programme effectiveness: Kota Belud primary school English teachers’ voice into perspective - Daraini Oyot; Roslee Talip (Malaysian Journal of Social Sciences and Humanities (MJSSH), 2022)
This research is conducted in order to identify teachers’ perception on the effectiveness of the ongoing Professional Development Programme among the primary school English teachers in Kota Belud, Sabah. This nonexperimental research applies survey method and a few sampling techniques in order to obtain the right size of the sample. The data is gathered using a set of questionnaires that has been adopted and are administered to 30 teachers in public primary schools. The data collected is then analysed using descriptive statistics using SPSS. The finding shows that there is no significant difference on the teachers’ perception regarding professional development programme effectiveness based on their gender and teaching experience. The implication and suggestion for further research are also discussed.